The role of teachers in developing noble character in early childhood education - Royana Ashari; Uswatun Hasanah; Yessy Andini Putri; Nur Aini; Nadia Arifatul Jannah (CV. SPDFHarmony, 2025)
Background: Early childhood education plays a vital role in the formation of noble moral character, as this stage strongly influences children’s attitudes, behaviors, and value internalization. Character development in early childhood is not formed through instruction alone, but through consistent habituation, role modeling, and meaningful social interaction. Teachers therefore hold a strategic position as educators and moral exemplars. However, empirical studies that specifically examine teachers’ everyday roles in shaping children’s noble moral character remain limited. Aims: This study aims to describe the roles of teachers in the development of noble moral character among early childhood learners, focusing on teachers’ functions as educators, role models, developmental planners, and consultants and mediators. Method: This study employed a descriptive qualitative research approach. Data were collected through semi-structured interviews, classroom observations, and documentation involving teachers at an early childhood education institution. Data analysis was conducted through data organization, description, and interpretation to obtain an in-depth understanding of teachers’ roles in character development. Results: The findings indicate that teachers play four main roles in developing noble moral character: educators who integrate moral values into learning activities, role models who demonstrate positive behavior, developmental planners who design character-oriented activities, and consultants and mediators who guide children in resolving social and emotional challenges. These roles are implemented through habituation, daily interaction, and collaboration with parents. Conclusion: Teachers play a crucial role in the development of noble moral character in early childhood education. Strengthening teachers’ competencies and maintaining collaboration between schools and families are essential to support sustainable character development in early childhood.